Dampak Implementasi Environmental Goods (EGS) List Terhadap Kinerja Perdagangan Indonesia - Rahmaniar Salam, Aziza; Adi Nugroho, Rino (Pusjar SKPP Lembaga Administrasi Negara, 2016)
Preparation of Environmental Goods list (EGs) and its implementation plan in international trade among APEC members will have impact on trade flows to the economics of its member, including Indonesia. This analysis aims to determine the potential impact that will be faced by Indonesia’s trade performance. This analysis used a Gravity model on 54 EGs products with GDP, value of imports, the distance and tariffs as variable. The analysis showed that GDP, value of imports and tariffs significantly affect Indonesian exports and imports, while distance has no significant effect either on export or import of Indonesia. Of the 48 products which can be processed, 38 products EGS will impact to increase Indonesia’s imports better rather than other APEC member, which in turn will lead trade balance into deficit. 10 products, providing the possibility of increasing Indonesian exports to APEC. Overall, EGS product is manufactured products produced by developed countries, so the elimination of tariffs provide less incentive for domestic producers to increase production to meet domestic and foreign demand. Indonesia should have initiative to create and strengthen domestic industries that are environmentally friendly, facilitating investment, deregulation of the domestic private sector to build and increase productivity.Keywords : APEC, Environmental Goods list, Indonesia trade performancePenyusunan Environmental Goods list (EGs) dan rencana implementasinya dalam perdagangan internasional antar negara APEC akan membawa dampak pada arus perdagangan yang selanjutnya pada perekonomian masing-masing anggota, termasuk Indonesia. Analisis ini bertujuan untuk mengetahui dampak potensial yang dihadapi Indonesia dengan diimplementasikannya EGs list terhadap kinerja perdagangan. Analisis ini menggunakan Gravity model pada 54 produk EGs dengan variabel PDB, nilai impor, jarak dan tarif bea masuk. Hasil analisis menunjukkan bahwa PDB, nilai impor dan tarif signifikan mempengaruhi ekspor dan impor Indonesia akan produk EGs, sedangkan jarak tidak berpengaruh signifikan baik terhadap ekspor maupun impor Indonesia. Dari 48 produk, yang dapat diolah, 38 produk EGs akan memberikan dampak pada meningkatnya impor Indonesia dari anggota APEC lainnya, yang pada akhirnya akan menyebabkan neraca perdagangan menjadi defisit. Sepuluh produk akan memberikan dampak kemungkinan terjadi peningkatan ekspor Indonesia ke negara APEC. Secara keseluruhan, produk EGs merupakan produk manufaktur yang dihasilkan oleh negara maju, sehingga penurunan tarif kurang memberikan insentif bagi produsen domestik untuk meningkatkan produksi dalam memenuhi permintaan domestik maupun asing. Indonesia harus memiliki inisiatif untuk menciptakan dan memperkuat industri domestik yang ramah lingkungan, memfasilitasi investasi, deregulasi untuk membangun sektor swasta domestik dan peningkatan produktivitas.Kata kunci: APEC, EGs list, Neraca Perdagangan Indonesia